Caracterização das viagens realizadas no município de Caraúbas/RN - Lopes, Thayse Silva (Universidade Federal Rural do Semi-Árido, 2018)
The development of a urban mobility planning requires series of studies, which the purpose is to understand the current situation of the region considered. Among the necessary studies, it is important to highlight the characterization of transport users, since the pattern of people displacement reflects the socioeconomic characteristics. In addition, characterizing the trips developed allows to locate where the goods and services of a given traffic zone are provided, which are the factors that generate travel. So, in order to diagnose the situation in the way to understand the current problems of mobility, the first step is to obtain and collect a series of data and information from all sectors of the urban environment, in relation to territorial factors; socioeconomic; generation and attraction of travel; availability of services, education, health and leisure; use and occupation of the soil, among others. In view of this, the present work sought to develop the proposed characterizations (of travel and socioeconomics) for the city of Caraúbas/RN, through the use of two databases. The 2010 demographic census, conducted by the IBGE, together with the development of a household survey, where 1,000 residential interviews were conducted through the application of questionnaires, subsidized the socioeconomic characterization of the population. While the characterization of the trips made, it was developed based on the data obtained during the application of the questionnaires. In the analysis phase, it was possible to perceive the unequal distribution of services and opportunities in the urban environment, besides a socioeconomic configuration based on the general situation of the country, where the population concentrated in the peripheral areas of the city. with a higher percentage of women and an irregular age pyramid, with an adult majority (18 to 59 years). The trips are developed according to the configuration of the city, given the unequal distribution of services, and it still influenced by the characteristics presented by the population. Based on the results obtained by this research, it is prudent to carry out the proposal of a mobility planning with the managers of the municipality, due to the importance of the topic addressed and the established indicators.
Monografia
Keywords: Mobilidade urbana; Fatores condicionantes da mobilidade; Zonas de tráfego; Viagens origem-destino; ENGENHARIAS::ENGENHARIA CIVIL